Risks of dental treatment in children with congenital heart disease and care needed to mitigate them (Research, Society and Development, 2024)
Congenital heart defects are diseases characterized by malformations in the structure or function of the heart. Global screening protocols designed for congenital malformations are needed to eliminate late diagnosis and prevent the operative risks of surgical procedures. The objective of our study is to guide the dental surgeon regarding the risks and how to proceed to mitigate these risks in dental treatment in children with congenital heart defects. A narrative literature review study was carried out. Many studies show that pediatric patients with coronary disease have significantly higher counts of dental caries and periodontitis than the healthy population, but there is controversy. Periodontal diseases, such as gingivitis and periodontitis, can also be linked to cardiac changes in predisposed patients, due to the use of different types of medications and insufficient consumption of healthy foods and minerals, they end up becoming a target. In addition, antibiotic prophylaxis to more invasive treatments. However, regardless of whether there are controversies, oral health information and care should be for everyone, these patients have more specific peculiarities and risks that require individualized care.